A Systematic Review of The Contribution of Google Docs in Teaching Writing Skill - Anindya Nur Islami Pratiwi; Citra Kusumaningsih; Dian Shinta Sari (XXXX-XXXX, 2021)
The research aimed to investigate the contribution of Google docs in teaching writing skill. This research reviewed the previous studies on Google docs in teaching writing skill which were published within the past ten years. This research used systematic review as the method. There were five from seventeen journals have been selected by hand searching based on inclusion exclusion criteria and fulfill the criteria from seventeen journals. Five studies were included and reviewed in terms of (i) population, (ii) comparison, (iii) outcomes, (iv) study design, (v) publication years, (vi) language. This research utilized internet searching to search the journals. To analyze the data, this research used thematic analysis as technique of analysis data. The result show that (1) Google docs helped students in writing process. (2) The successful of Google docs provided by students’ scores increased. (3) Google docs encourage students’ motivation, interest, and communication. Further, Google docs were helpful, useful, and enjoyable tool for students to improve their writing skill.    Keywords: systematic review, Google docs, writing skill.